(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This research investigated the effect of the use of black seed powder, cinnamon, yeast and their mixtures on the productive performance of the Rose meat breeds, where they distributed 240of one day old 40gm/chick body weight (Ross strain) randomly on 8 treatments , each treatment included two replicate (15chicks/replicate) and fed on standard diet with addition 0.05% yeast Saccharomyces cerevisiae to second treatment , 0.4%cinnamon powder to third treatment, 0.4% black seed powder to fourth treatment 0.2% Cinnamon powder mixture with 0.025% yeast for the fifth treatment, 0.2% for each cinnamon black seed powder mixture, for the sixth treatment, 0.025% yeast mixture with 0.2%black seed powder for the seventh treatment, the triple mixture of 0.025% yeast and0.2% for each cinnamon black seed powder for the eighth treatment, and the first treatment was left on the ordinary diet without addition as control. Weekly weights with weekly and total weight gain, weekly and the total feed consumption rate, weekly and the total dietary conversion efficiency were calculated. The results showed significant differences in weekly weight rate weekly and total weights gain toward the treatments (T3, T4, T6, T7, T8) compared with the control treatment (T1) and were not significant with the second and fifth treatments (T2, T5) and the last two treatments were not related Significant differences with control treatment in these two characters, As well as the results showed no significant differences in feed consumption between the additional treatment and control factors, except for the third treatment containing 0.4% cinnamon powder. The cinnamon powder had significant differences compared to the control treatment in feed consumption rate and was not significant with the rest of the additive treatments. as well as the results showed that there was a significant decrease in the conversion efficiency of all additive treatments compared to control treatment (T1) and the best of the results toward the fourth treatment (adding black seed powder) was signed with the first treatment (control) and the second(yeast addition). and was not significant with the rest of the additive treatments.